STUDENT DEVELOPMENT OF ELEMENTARY SCHOOL 060878 IN LEARNING ENGLISH - Eva Betty Simanjuntak; Okmika Greselly; Bonita Situmorang; Baihaqi Muhamad; Boby Saputra (Indonesian Journal of Elementary Education (IJETE), 2025)
This research examines the development of English language skills among students at Elementary School 060878, focusing on challenges, influencing factors, and effective teaching strategies. A mixed-method approach was employed, combining quantitative data from student test scores and qualitative data from teacher interviews and classroom observations. The results indicate that students face difficulties in vocabulary mastery and speaking skills, influenced by limited exposure to English, traditional teaching methods, and psychological barriers. The study proposes interactive and student-centered strategies, such as project-based learning and digital media, to enhance engagement and outcomes. These findings provide insights for teachers and policymakers to improve English language instruction in elementary schools.